Immune reconstitution and associated infections following axicabtagene ciloleucel in relapsed or refractory large B-cell lymphoma - Logue, Jennifer M; Zucchetti, Elisa; Bachmeier, Christina A; Krivenko, Gabriel S; Larson, Victoria; Ninh, Daniel; Grillo, Giovanni; Cao, Biwei; Kim, Jongphil; Chavez, Julio C; Baluch, Aliyah; Khimani, Farhad; et al. (Haematologica (Roma), 2021)
CD19 CAR T-cell therapy with axicabtagene ciloleucel (axi-cel) for relapsed or refractory (R/R) large B cell lymphoma (LBCL) may lead to durable remissions, however, prolonged cytopenias and infections may occur. In this single center retrospective study of 85 patients, we characterized immune reconstitution and infections for patients remaining in remission after axi-cel for LBCL. Prolonged cytopenias (those occurring at or after day 30 following infusion) were common with >= grade 3 neutropenia seen in 21/70 (30-0%) patients at day 30 and persisting in 3/31 (9-7%) patients at 1 year. B cells were undetectable in 30/34 (88-2%) patients at day 30, but were detected in 11/19 (57-9%) at 1 year. Median IgG levels reached a nadir at day 180. By contrast, CD4 T cells decreased from baseline and were persistently low with a median CD4 count of 155 cells/μl at 1 year after axi-cel (n=19, range 33 – 269). In total, 23/85 (27-1%) patients received IVIG after axi-cel, and 34/85 (40-0%) received G-CSF. Infections in the first 30 days occurred in 31/85 (36-5%) patients, of which 11/85 (12-9%) required intravenous antibiotics or hospitalization (“severe”) and were associated with cytokine release syndrome (CRS), neurotoxicity, tocilizumab use, corticosteroid use, and bridging therapy on univariate analyses. After day 30, 7 severe infections occurred, with no late deaths due to infection. Prolonged cytopenias are common following axi-cel therapy for LBCL and typically recover with time. Most patients experience profound and prolonged CD4 T cell immunosuppression without severe infection.